2023
DOI: 10.1002/ps.7616
|View full text |Cite
|
Sign up to set email alerts
|

Resistant risk and resistance‐related point mutation in SdhC1 of pydiflumetofen in Fusarium pseudograminearum

Abstract: BACKGROUNDFusarium pseudograminearum is one of the dominant pathogens of Fusarium crown rot (FCR) worldwide. Unfortunately, no fungicides have yet been registered for the control of FCR in wheat in China. Pydiflumetofen, a new‐generation succinate dehydrogenase inhibitor, exhibits excellent inhibitory activity to Fusarium spp. A resistance risk assessment of F. pseudograminearum to pydiflumetofen and the resistance mechanism involved have not yet been investigated.RESULTSThe median effective concentration (EC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…To date, pydiflumetofen (PYD), a novel succinate dehydrogenase inhibitor, is the only SDHI fungicide registered for controlling wheat FHB with excellent efficacy in the field. , However, the PYD resistance was reported in another phytopathogenic fungi, including F. graminearum, Fusarium pseudograminearum, Fusarium fujikuroi, Botrytis cinerea, Magnaporthe oryzae, and Didymella bryoniae. Our previous study showed that SdhB H248Y , SdhC 1 A64V , or SdhC 1 R67K mutations are responsible for the resistance to PYD in F. asiaticum .…”
Section: Introductionmentioning
confidence: 99%
“…To date, pydiflumetofen (PYD), a novel succinate dehydrogenase inhibitor, is the only SDHI fungicide registered for controlling wheat FHB with excellent efficacy in the field. , However, the PYD resistance was reported in another phytopathogenic fungi, including F. graminearum, Fusarium pseudograminearum, Fusarium fujikuroi, Botrytis cinerea, Magnaporthe oryzae, and Didymella bryoniae. Our previous study showed that SdhB H248Y , SdhC 1 A64V , or SdhC 1 R67K mutations are responsible for the resistance to PYD in F. asiaticum .…”
Section: Introductionmentioning
confidence: 99%